2009
DOI: 10.1007/s12665-009-0091-8
|View full text |Cite
|
Sign up to set email alerts
|

Desalination of a sedimentary rock aquifer system invaded by Pleistocene Champlain Sea water and processes controlling groundwater geochemistry

Abstract: The objective of this study was to identify geochemical processes and Quaternary geological events responsible for the variations in groundwater geochemistry observed in a sedimentary rock aquifer system, including brackish to saline groundwater. Inorganic constituents and environmental isotopes were analyzed for 146 groundwater samples. Dissolution of carbonates dominates in recharge areas, resulting in Ca-, Mg-HCO 3 groundwater. Further along flow paths, under confined conditions, Ca 2? -Na ? ion exchange ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 25 publications
0
49
0
2
Order By: Relevance
“…Note that only the flow path A-A' is discussed in this paper. This approach supported the development of a conceptual model of the geochemical evolution of groundwater, which was compared to the conceptual model of the BassesLaurentides area developed previously by Cloutier et al (2010).…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…Note that only the flow path A-A' is discussed in this paper. This approach supported the development of a conceptual model of the geochemical evolution of groundwater, which was compared to the conceptual model of the BassesLaurentides area developed previously by Cloutier et al (2010).…”
Section: Introductionmentioning
confidence: 84%
“…It can be concluded that the conditions present in the groundwater flow system in the Chateauguay River watershed allows more flushing of Champlain Sea water compared to the Basses-Laurentides, thus leading to the main differences observed in the groundwater geochemistry of these two areas. Areas of reduced flushing in BassesLaurentides are related to convergentdivergent groundwater flow patterns in two buried valleys of the Basses-Laurentides (Cloutier et al, 2010). Such flow patterns are not observed in the Chateauguay River, which has continuous flow paths leading to significant flushing of the entire aquifer system, thus reducing the sea water imprint on groundwater geochemistry.…”
Section: Geochemical Conceptual Modelmentioning
confidence: 96%
See 3 more Smart Citations